Democratic countries and ways of influencing the nature of information - Kazimi, Parviz Firudin Oqlu (Technium Social Sciences Journal, 2021)
The repertoire of library and information resources, the organization of information services and the acquisition of sources in the implementation of library policy are based on historical traditions. In the digital space and in the globalizing world, this process has changed both its form and its essence. It is known that throughout history, information resources have been censored and restricted. While these censorship restrictions are sometimes considered severe and sometimes insignificant, this problem arises and raises questions during the "dissemination" and "promotion" of information. The issue of limiting information and prohibiting its dissemination in the global information space remains relevant today. These restrictions can, at the request of a number of states, limit the scope of religious beliefs, as well as court decisions. Local, regional representations can also meet a number of restrictive requirements. I think that when it comes to free and democratic circulation of information products in the information space, it is necessary to define a mathematical model of how democratic it is. This article can be seen as a summary of the existing experience in this area